The “The Acronyms Club” Has the Ukraine Conflict Exposed the West and its History? The Most Comprehensive Study into How U.S. Hegemony Denies Sovereignties of Nations. - Miller, Antony D.; Illipinar, Gürsel (International Journal of Scientific Research and Management (IJSRM), 2022)
Von Clausewits once wrote [in many of his aphorisms]: “War is the continuation of policy with other means.” (Howard; Paret 1974,). Firstly, this comprehensive body of research is an empirical attempt to purposely examine for the first time, how the West has continued to influence many countries without honouring their sovereignty. Secondly, this paper aims to validate, that the Russian Federation, made the correct decision by escalating the 8-year conflict in Ukraine, as a protectionary measure, thus, confirming the globe’s new “multipolarity” simultaneously; since the inception of military activities. Furthermore, this study will illustrate the decline of a unipolar world additionally via the US Dollar weaponization policies, resulting in denying sovereign states their dignity, from continuing confirmed illegal punitive sanctions. Thirdly, has both the three-year [SARS-CoV-2] pandemic, and the following Ukraine conflict, exposed the West’s true nature of an immoral gambit’s true nature more publicly? Referring to “The Acronyms Club”: US, UN, EU, NATO, IMF, WB and the OSCE, -has it been exposed within its hegemonic conduct, since the cessation of the Cold War? Fourth, it will be confirmed via documented history and acts recently that the UN Charter System i.e., Articles 3, 6, have been ignored on many fronts, consequently, the organization has become redundant and untruthful in today’s epoch. Fifth, this objectional hypothesis will notate the historic factors which has led to distrust of western society, by eastern states; mainly due to its Western leadership of false promises with misinformation. Thus, has Russia’s action exposed an inflection point within the West and neo-liberal economic policy? Finally, the hypothesis being, why had the Russian Federation, purposely venture into Ukrainian territory, via “Special Military Operations” and was there provocation prior to doing so? Finally, has the Acronyms Club inadvertently created a “Cold War” 2.0 within Eastern reviewed trading practice?